2013
DOI: 10.3109/02699206.2013.791880
|View full text |Cite
|
Sign up to set email alerts
|

Intervention for improving comprehension in 4–6 year old children with specific language impairment: practicing inferencing is a good thing

Abstract: Few studies report on therapy to improve language comprehension in children with specific language impairment (SLI). We address this gap by measuring the effect of a systematic intervention to improve inferential comprehension using dialogic reading tasks in conjunction with pre-determined questions and cues. Sixteen children with a diagnosis of SLI aged 4-6 participated in 10 weekly treatment sessions carried out by their regular therapists. Baseline and maintenance periods were also tabulated. Two experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…Understanding inferences can be measured in young children through different types of questions related to the story (Desmarais et al . , Ford and Milosky , 2008, Makdissi and Boisclair , Trabasso and Nickels , van Kleeck et al . , van Kleeck , Wenner ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding inferences can be measured in young children through different types of questions related to the story (Desmarais et al . , Ford and Milosky , 2008, Makdissi and Boisclair , Trabasso and Nickels , van Kleeck et al . , van Kleeck , Wenner ).…”
Section: Introductionmentioning
confidence: 99%
“…The studies investigating causal inferences in children aged 4–6 years have shown inferences related to story grammar appear early and can be measured in a dialogic reading context (Das Gupta and Bryant , Desmarais et al . , Kendeou et al . , van Kleeck ).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of interventions to address early literacy skills in children with language delays and disorders have been investigated, including phonological awareness interventions, 11,12 shared or interactive book reading, 13,14 sight word instruction, 15,16 vocabulary instruction, 17 and print awareness interventions. 18,19 Remediation, however, is often challenging.…”
Section: Early Literacy Skills Of Children With Language Delays and Dmentioning
confidence: 99%
“…The implementation of interactive reading activities by parents and speech-language pathologists has frequently been demonstrated to result in increases in both language and literacy skills for young children with language delays and disorders, although not all interventions have resulted in the targeted outcomes. [12][13][14]19,[26][27][28] Table 1 provides an overview of recent research on the impact of interactive reading interventions with young children (ages 3 years; 2 months to 6 years; 5 months) with language delays and disorders. These seven studies describe the use of a wide variety of partner reading behaviors during interactive reading (e.g., asking ques-tions, giving feedback to the child, directing the child's attention to features of the text).…”
Section: Interactive Reading For Children With Language Delays and DImentioning
confidence: 99%
“…one of the easiest ways to bolster comprehension instruction for young children is to intensify the quality and quantity of interactive read-alouds conducted by adults both at school and at home (see Stahl, 2014;Stahl & García, 2015). robust research evidence indicates that providing a small-group interactive read-aloud intervention will increase performance in comprehension, general language abilities, vocabulary, and phonological awareness for children with literacy difficulties and more severe specific language impairment (Desmarais, Nadeau, trudeau, Filiatrault-Veilleux, & Maxès-Fournier, 2013;Swanson et al, 2011;Van Kleeck, Vander woude, & Hammett, 2006;whitehurst et al, 1994).…”
Section: Interventions To Improve Narrative Comprehensionmentioning
confidence: 99%